Impacts of sulfate polysaccharide JCS1S2 on retinal neovascularization in oxygen-induced retinopathy rats - Bai, Yang; Wang, Rui; Jin, Can; Wang, Lili; Tang, Yun; Wang, Han; Ding, Kan; Cai, Shanjun (Frontiers in Pharmacology, 2025)
Retinal neovascularization, a pathological form of angiogenesis, is a leading cause of blindness. This study investigated the effects of Dendrobium sulfate polysaccharide JCS1S2, derived from Dendrobium chrysogenum, on oxygen-induced retinopathy (OIR) in rat models and Müller cells of the rat retina. To this end, we established an OIR rat model and divided the rats into three primary groups, namely, Group I (control), Group II (OIR), and Group III (OIR + JCS1S2). Group III was further subdivided into three subgroups treated with different concentrations of JCS1S2 (10 μg/μL, 20 μg/μL, and 40 μg/μL). After finding the optimal concentration of JCS1S2 by ADP and HE, PCR, Western blot and transcriptome sequencing were used to analyze the role of JCS1S2 in Müller cells of OIR rats and rat retinas. ADP and hematoxylin and eosin (HE) staining revealed that JCS1S2 dose-dependently inhibited retinal neovascularization. Quantitative polymerase chain reaction (qPCR) and Western blot analyses showed significant downregulation of vascular endothelial growth factor A (VEGF-A), VEGF-B, VEGF-D, VEGF receptor 1 (VEGF-R1), and VEGF receptor 2 (VEGF-R2) following JCS1S2 treatment. Transcriptome analysis suggested that JCS1S2 may suppress the activation of the Toll-like receptor (TLR) signaling pathway, regulate the expression of genes associated with endothelial activation and angiogenesis, and participate in the inflammatory and metabolic pathways of the retina. Western blotting data indicate that JCS1S2 can markedly reduce abnormal retinal angiogenesis and Müller cell activation in OIR rats through the TLR4/p-NF-κB/VEGF pathway, JCS1S2 may have the potential as a therapeutic agent for retinal neovascularization.